Long-Term Monitoring Reliability and Life Prediction of Fiber Bragg Grating-Based Self-Sensing Steel Strands - Heying Qin; Quanxi Shen; Jinping Ou; Wanxu Zhu (Advances in Civil Engineering)
To analyze the long-term monitoring reliability and life expectancy of FBG-based steel strands, accelerated corrosion and tensile tests were carried out and a life-prediction model was constructed. The validation test results indicated that the monitoring strain sensitivity of FBG-based steel strands decreases with an increase in solution concentration and time in a corrosive acidic environment. When the sensitivity dropped to about 80% of its initial value, the FBG sensor suddenly failed. The life-prediction model indicates that the predicted monitoring life of an FBG sensor is about 56 years in an unstressed condition but about 27 years under the stressful conditions that FBG-based steel strands are subjected to in their working environment. So, to improve their monitoring reliability and monitoring life, it is suggested that FBG-based steel strands might be prepared by “pre-loading.”